2011
DOI: 10.4028/www.scientific.net/amr.194-196.1724
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in the Thermal Shock Resistance of Zirconia Ceramic by the Addition of Aluminium Titanate

Abstract: ZrO2-Al2TiO5 composite materials with high bending strength and good thermal shock resistance expansion were prepared using partially stabilized zirconia (Y-PSZ) powders coated with Al2TiO5 by co-precipitation method. The effects of Al2TiO5 content on the sintering properties, phase composition, microstructure and thermal shock resistance of the zirconia ceramic were investigated.The results show that the apparent porosity of the samples decreased and their bending strength increased with the content of alumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…They are widely used in industrial high-temperature furnace linings [11], such as crystal growth furnaces and ultra-high temperature sintering furnaces [12]. However, the thermal shock resistance of ZrO 2 berboards at high temperature is unsatisfactory, and its poor thermal shock resistance is mainly due to the large volume change caused by its high thermal expansion coe cient [13][14]. Under the condition of thermal shock, the high thermal expansion coe cient of the stable ZrO 2 induces larger thermal stress.…”
Section: Introductionmentioning
confidence: 99%
“…They are widely used in industrial high-temperature furnace linings [11], such as crystal growth furnaces and ultra-high temperature sintering furnaces [12]. However, the thermal shock resistance of ZrO 2 berboards at high temperature is unsatisfactory, and its poor thermal shock resistance is mainly due to the large volume change caused by its high thermal expansion coe cient [13][14]. Under the condition of thermal shock, the high thermal expansion coe cient of the stable ZrO 2 induces larger thermal stress.…”
Section: Introductionmentioning
confidence: 99%
“…These properties make Al2TiO5 a good choice for high-temperature applications such as exhaust port liners, valves, turbochargers, piston buttons, manifold insulations, swirl chambers and other internal combustion engines components. Moreover, aluminium titanate ceramics are suitable materials in many other crucial applications such as in burner nozzles, thermocouple sleeves and refractory crucibles for metal casting and flow regulations [15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, Wei et al prepared ZrO 2 Al 2 TiO 5 composite materials with high bending strength and good thermal shock resistance expansion using partially stabilized zirconia (Y-PSZ) powders coated with Al 2 TiO 5 by co-precipitation method [12]. Shimada et al found that aluminium titanate was strengthened by alloying with 3 mol.% yttria stabilized zirconia to attain a small expansion coecient of 2 × 10 −6 and a high strength of 100 MPa [13].…”
Section: Introductionmentioning
confidence: 99%